The Consequences of Child Labor : Evidence from Longitudinal Data in Rural Tanzania - Beegle, Kathleen; Dehejia, Rajeev H.; Gatti, Roberta; Krutikova, Sofya (World Bank, Washington, DC, 2012)
This paper exploits a unique longitudinal data set from Tanzania to examine the consequences of child labor on education, employment choices, and marital status over a 10-year horizon. Shocks to crop production and rainfall are used as instrumental variables for child labor. For boys, the findings show that a one-standard-deviation (5.7 hour) increase in child labor leads 10 years later to a loss of approximately one year of schooling and to a substantial increase in the likelihood of farming and of marrying at a younger age. Strikingly, there are no significant effects on education for girls, but there is a significant increase in the likelihood of marrying young. The findings also show that crop shocks lead to an increase in agricultural work for boys and instead lead to an increase in chore hours for girls. The results are consistent with education being a lower priority for girls and/or with chores causing less disruption for education than agricultural work. The increased chore hours could also account for the results on marriage for girls.